Spatial Heterogeneity of Forest-Steppes - Erdos, Laszlo (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Forest-steppes occupy a wide zone between Eurasian closed canopy forests and open steppes and feature a mosaic of woody and herbaceous vegetation. Due to the occurrence of structurally, compositionally, and environmentally strongly different habitats in close proximity, high spatial heterogeneity is one of the key characteristics of forest-steppe ecosystems. This volume presents ten contributions examining forest-steppe heterogeneity and its effects on environmental factors, plant communities, and animals.